Values in Change: A Panel Study of German Youth, 1976-79. - United States. International Communication Agency. Office of Research.; Dalton, Russell J. (Tufts University. Tisch Library., 2019)
This report examines these German youth surveys [surveyed in a two-wave panel study between 1976 and 1979], with a special attention on foreign policy opinions. We explore general orientations toward the United States and other nations. Specific foreign policy issues such as NATO, human rights, and the perceived role for the Federal Republic in world affairs are also examined.; Related data is available at GESIS Leibniz Institute for the Social Sciences: https://search.gesis.org/publication/gesis-bib-103695.